Um sistema de conversão de energia eólica de 53kw conectado à rede elétrica utilizando um emulador de turbina eólica - Sousa, Jefferson Maia de (2021)
With the increasing production of electric energy using wind energy, power electronics presents a great collaboration with the connection of this energy source to the electrical grid, and there is a need to test these converters in reduced spaces and at a lower cost for different wind profiles. In this context, this work aims to propose a 53kW wind energy conversion system with a wind turbine emulator. For the emulator, a 100 cv threephase induction motor from the manufacturer WEG is used, a gearbox to reduce the rotation speed and increase the torque and a WEG CFW-09 inverter to control the motor and ensure that it has the same torque-speed characteristics of a real turbine. A 53 kW permanent magnet synchronous generator (PMSG) is used to convert mechanical energy into electrical energy with an electronic power converter for connection to the electrical grid. The converter operates with the variable frequency of the PMSG voltage and features two power conversion stage (AC/DC and DC/AC). The first conversion stage consists of three single-phase boost bridgeless rectifiers, one per phase, which uses the synchronous inductances of the PMSG itself as an energy storage element and for power factor correction. The second conversion stage is composed of a full-bridge three-phase voltage inverter with an inductive filter. The wind turbine emulation system is presented, from the details of its physical construction, the turbine modeling and the application developed in LABVIEW. The work analyzes the modeling and carrier modulation of the rectifier stage, the dq modeling and the spatial vector modulation of the inverter. Converter validation is done by simulation in PSIM software. The simulations are performed for several operating points with different frequencies and powers, with THD values below 5% and high power factor, both in the current on the PMSG side and on the grid side